Polymorphic Mutation Frequencies in Escherichia coli: Emergence of Weak Mutators in Clinical Isolates - Baquero, María-Rosario (American Society for Microbiology, 2004)
Polymorphisms in the rifampin resistance mutation frequency (f) were studied in 696 Escherichia coli strains from Spain, Sweden, and Denmark. Of the 696 strains, 23% were weakly hypermutable (4 × 10(−8) ≤ f < 4 × 10(−7)), and 0.7% were strongly hypermutable (f ≥ 4 × 10(−7)). Weak mutators were apparently more frequent in southern Europe and in blood isolates (38%) than in urinary tract isolates (25%) and feces of healthy volunteers (11%).